Quantum effects on dislocation motion from ring-polymer molecular dynamics. (December 2018) - Freitas, Rodrigo; Asta, Mark; Bulatov, Vasily
Abstract Quantum motion of atoms known as zero-point vibration was recently proposed to explain a long-standing discrepancy between theoretically computed and experimentally measured low-temperature plastic strength of iron and possibly other metals with high atomic masses. This finding challenges the traditional notion that quantum motion of atoms is relatively unimportant in solids comprised of heavy atoms. Here we report quantum dynamic simulations of quantum effects on dislocation motion within the exact formalism of Ring-Polymer Molecular Dynamics (RPMD). To extend the reach of quantum atomistic simulations to length and time scales relevant for extended defects in materials, we implemented RPMD in the open-source code LAMMPS thus making the RPMD method widely available to the community. We use our RPMD/LAMMPS approach for direct calculations of dislocation mobility and its effects on the yield strength ofα -iron. Our simulation results establish that quantum effects are noticeable at temperatures below 50 K but account for only a modest (≈13% atT = 0 K) overall reduction in the Peierls barrier, at variance with the factor of two reduction predicted earlier based on the more approximate framework of harmonic transition state theory. Our results confirm that zero-point vibrations provide ample additional agitation for atomic motion that increases with decreasing temperature, however its enhancing effect on dislocation mobility is largely offset by an increase in the effective atom size, an effect known as quantum dispersion that has not been accounted for in the previous calculations. Dislocations: ring-polymer molecular dynamics incorporates quantum effects Large ring-polymer molecular dynamics can accurately simulate quantum effects on dislocation motion. A team led by Rodrigo Freitas at the University of California, Berkeley and Lawrence Livermore National Laboratory, U.S.A., investigated the effect of atomic quantum motion on the Peirels stress, i.e., the low-temperature resistance to dislocation motion. While classical molecular dynamics yielded the expected overestimation of the Peirels stress compared to experiments, ring-polymer molecular dynamics on 150, 000 atoms using parallel computing showed a smaller discrepancy between simulations and experiments. This indicated that earlier quantum corrections overestimated the agitation effect of zero-point-vibrations and downplayed the effect of atomic neighbor confinement. Implementing efficient ring-polymer molecular dynamics can help us study extended defects in materials, while accurately accounting for quantum corrections to atom dynamics.